2021
DOI: 10.1590/0001-3765202120210171
|View full text |Cite
|
Sign up to set email alerts
|

Multiple reaction monitoring tool applied in the geochemical investigation of a mysterious oil spill in northeast Brazil

Abstract: In 2019, much of the northeastern coast of Brazil was impacted by a mysterious oil spill that caused an environmental disaster affecting 1009 beaches. Four samples were collected in the beaches between Sergipe and Pernambuco for geochemical characterization of the spilled oil and to compare with those main produced in Sergipe-Alagoas basin. Our approach in this evaluation was the use of a highly selective technique of sequential mass spectrometry by multiple reaction monitoring, to obtain the diagnostic ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 38 publications
(67 reference statements)
0
21
0
Order By: Relevance
“…Given the differences in GC-FID traces (Figure ), we performed additional compositional analysis to determine if our samples shared the same source as those of Lourenço et al (2020), Oliveira et al (2020), and Carregosa et al (2021). ,, Quantitative analysis of diagnostic ratios supported the qualitative differences observed in GC-FID and GC×GC-FID chromatograms from Lourenço et al (2020), Oliveira et al (2020), and Carregosa et al (2021) (Figure ). ,, A comparison of overlapping diagnostic ratios in the aforementioned studies is listed in Table S4. An expanded list of ratios from GC×GC-FID revealed that our 12 samples were similar and had relative standard deviations of less than 10% for all but the oleanane/hopane (O/H) ratio, which had a relative standard deviation of 15%.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…Given the differences in GC-FID traces (Figure ), we performed additional compositional analysis to determine if our samples shared the same source as those of Lourenço et al (2020), Oliveira et al (2020), and Carregosa et al (2021). ,, Quantitative analysis of diagnostic ratios supported the qualitative differences observed in GC-FID and GC×GC-FID chromatograms from Lourenço et al (2020), Oliveira et al (2020), and Carregosa et al (2021) (Figure ). ,, A comparison of overlapping diagnostic ratios in the aforementioned studies is listed in Table S4. An expanded list of ratios from GC×GC-FID revealed that our 12 samples were similar and had relative standard deviations of less than 10% for all but the oleanane/hopane (O/H) ratio, which had a relative standard deviation of 15%.…”
Section: Resultsmentioning
confidence: 55%
“…Map of Brazilian coastline with locations of reported oiling (red line) and field samples from this study (yellow circle), de Oliveira et al, 2020 (green circles), Lourenço et al, 2020 (purple circles), and Carregosa et al, 2021 (blue circles) . See Figure S1 and Table S1 for additional details on the locations and analyses performed on each sample in this study.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The original hypotheses regarding the origin of this mysterious oil spill were as follows: (1) It came from natural sources (e.g., asphalt seep sites) in Brazil or Africa; (2) the oil spilled from platforms in Brazil or Africa; (3) the oil spilled (intentionally or not) from ships in transit off the Brazilian coast; and (4) the oil came from shipwrecks (recent or old) (Escobar 2019;Soares et al 2020a, b). Geochemical and biomarker analyses of sedimentary basins indicated that the oil originated from Venezuelan sedimentary oil basins (e.g., Ayacucho oil, from Naricual Formation in Venezeluan Eastern basin); therefore, hypotheses 1 and 2 were discarded (Lourenço et al 2020;Oliveira et al 2020;Carregosa et al 2021;Zacharias et al 2021a, b). Currently, hypotheses 3 and 4 remain with ongoing and intense debate.…”
Section: Oil and Source Of Origin: An Unsolved Puzzlementioning
confidence: 99%